Resilience as a Preventive Factor in Early Childhood Psychosis - Hendy Yogya (HM Publisher, 2021)
Resilience is a person's ability to survive, rise, and adapt to difficult conditions. Individuals who have resilience are able to quickly return to their pre-psychic trauma, appear immune from negative life events, and are able to adapt to extreme stress and suffering. A child with disabilities, from an early age, the parents have to